Leaf-Rolling Weevil, Homoeolabus analis (Illiger) (Coleoptera: Attelabidae: Attelabinae) and Thief Weevil, Pterocolus ovatus Fabricius (Coleoptera: Rhynchitidae: Pterocolinae) - Donald W. Hall; Lyle Buss (EDIS)
This document provides an overview of the leaf-rolling weevil (Homoeolabus analis) and the thief weevil (Pterocolus ovatus) in Florida. It details their identification, distribution, and life cycle, including the unique nidification behavior of H. analis. The document also discusses the ecological interactions between these species, particularly the kleptoparasitic relationship of P. ovatus with H. analis. Additionally, it highlights management strategies and the minimal impact these weevils have on their host plants. Published: September 2007.